Teachers' Efforts in Strengthening Religious Moderation in Character Formation of Students at SD Negeri 2 Rukti Endah - Nurwahid H; Irhamudin; Adi Wijaya (Institut Agama Islam Ma`arif NU (IAIMNU) Metro Lampung, 2026)
This study aims to describe teachers' efforts in strengthening religious moderation towards the formation of student character and identify supporting and inhibiting factors at SD Negeri 2 Rukti Endah. This study uses a qualitative approach with the type of Classroom Action Research (CAR) model Kemmis and McTaggart which is implemented in two cycles through the stages of planning, implementation, observation, and reflection. Data collection techniques are carried out through observation, interviews, questionnaires, and documentation, while data analysis uses the interactive model of Miles and Huberman and percentage analysis to measure changes in students' tolerance character. The results of the study indicate that the application of the Problem Based Learning method and role playing is effective in improving students' tolerance character, which is demonstrated through the habit of saying salam, praying before and after studying, carrying out religious worship, and appreciating the celebration of religious holidays. This study shows that students not only understand the concept of tolerance theoretically, but are also able to implement it in everyday life, which reflects the values ​​of tasamuh, musawah, shura, and tahadhdhur. Supporting factors include a multicultural school environment, inclusive policies, participatory learning strategies, and teacher role models. While inhibiting factors include limited time, the absence of structured programs, lack of teacher training, and external environmental influences. Overall, this study emphasizes the importance of contextual and experiential learning in strengthening religious moderation and the need for collaboration between schools, teachers, and parents in shaping students' character.